2001
DOI: 10.4049/jimmunol.167.3.1325
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of Channel Catfish CTL with Respect to Target Recognition and Cytotoxic Mechanisms Employed

Abstract: Two types of catfish alloantigen-dependent cytotoxic T cells were cloned from PBL from a fish immunized in vivo and stimulated in vitro with the allogeneic B cell line 3B11. Because these are the first clonal cytotoxic T cell lines derived from an ectothermic vertebrate, studies were undertaken to characterize their recognition and cytotoxic mechanisms. The first type of CTL (group I) shows strict alloantigen specificity, i.e., they specifically kill and proliferate only in response to 3B11 cells. The second t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(37 citation statements)
references
References 46 publications
0
37
0
Order By: Relevance
“…The lines are classified as non-autonomous because occasional stimulation with the allogeneic 3B11 cells is required. 124 The vast majority of the clones were CTLs; however, one clone, which expressed TCRab, did not exhibit cytolytic activity but exerted a proliferative response to the presence of 3B11 cells and was classified as a putative alloantigen-specific T helper cell. 122 In mammals and birds, ab T cell subsets are defined by CD4 or CD8 expression, which signify T helper cells and cytotoxic T cells, respectively.…”
Section: Ab T Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…The lines are classified as non-autonomous because occasional stimulation with the allogeneic 3B11 cells is required. 124 The vast majority of the clones were CTLs; however, one clone, which expressed TCRab, did not exhibit cytolytic activity but exerted a proliferative response to the presence of 3B11 cells and was classified as a putative alloantigen-specific T helper cell. 122 In mammals and birds, ab T cell subsets are defined by CD4 or CD8 expression, which signify T helper cells and cytotoxic T cells, respectively.…”
Section: Ab T Cellsmentioning
confidence: 99%
“…108,119,120 The unequivocal confirmation of T cells in channel catfish can be ascribed to the cloning of TCRa and TCRb genes and the establishment of clonal T cell lines. [121][122][123][124] Indeed, much of what is known regarding catfish T cells arose from the development of these T cell lines, which were produced by limiting dilutions of peripheral blood lymphocytes (PBL) isolated from a single fish that had been immunized repeatedly with the catfish autonomous B cell line 3B11. 122 While not focused on mucosal populations, this landmark work on catfish cytolytic cells highlighted populations of CTLs based on alloreactivity and TCRab expression.…”
Section: Ab T Cellsmentioning
confidence: 99%
“…Although the granule content of teleost NK and Tc cells have not been formally proven, Zhou et al and Shen et al demonstrated that clonal catfish NK and Tc cells contain granules and kill allogeneic targets by an apoptotic mechanism that involves DNA fragmentation. Moreover, the killing can be completely inhibited by chelating extracellular calcium [28,29]. These findings strongly suggest that the killing is mediated exclusively by the secretory perforin/granzyme mechanism.…”
Section: Introductionmentioning
confidence: 77%
“…Because no evidence of the existence of the key molecules has been demonstrated in invertebrates and jawless vertebrates (1,5), it is generally believed that the AIS first emerged in jawed vertebrate fish (2). The CTL response plays a critical role in the AIS against viral infection and tumors (69,70). Although some studies have referred to the cloning of CTL response genes, such as class I, TAP, and TCR, and have extended the research on cell-mediated cytotoxicity in bony fish (4,56,71), class I-restricted Ag presentation has not been studied until now.…”
Section: Discussionmentioning
confidence: 99%